PROBLEMS OF DEVELOPING ECOTOURISM AND THE TECHNOLOGY OF USING NATURAL RESOURCES IN THE TERRITORIES OF SURKHANDARYA REGION - Bunyod O‘tkirovich Abdullayev (American Journals, 2025)
The article provides a comprehensive overview of the problems of developing ecological tourism and natural resource utilization technologies in the Surkhandarya region, the positive and negative consequences of the development of ecological tourism, the SWOT analysis of ecological tourism, ways to solve the problems of developing ecological tourism, the necessary conditions for forming a program for developing ecological tourism in the regions, and the main tasks of the "Green Step into the Future" ecological tourism development program.
Keywords: Tourism, productivity, tourists, hotel, infrastructure, assessment, index.